Toxic mechanism in Daphnia magna due to phthalic acid esters and CuO nanoparticles co-exposure: The insight of physiological, microbiomic and metabolomic profiles - Xu Jin; Junlan Pan; Cheng Zhang; Xuesong Cao; Chuanxi Wang; Le Yue; Xiaona Li; Yinglin Liu; Zhenyu Wang (Ecotoxicology and Environmental Safety, 2024)
Various phthalic acid esters (PAEs) such as dibutyl phthalate (DBP) and butyl benzyl phthalate (BBP) co-exist with nanopollutants in aquatic environment. In this study, Daphnia magna was exposed to nano-CuO and DBP or BBP at environmental relevant concentrations for 21-days to investigate these combined toxic effects. Acute EC50 values (48 h) of nano-CuO, DBP, and BBP were 12.572 mg/L, 8.978 mg/L, and 4.785 mg/L, respectively. Results showed that co-exposure with nano-CuO (500 μg/L) for 21 days significantly enhanced the toxicity of DBP (100 μg/L) and BBP (100 μg/L) to Daphnia magna by 18.37% and 18.11%, respectively. The activities of superoxide dismutase, catalase, and glutathione S-transferase were enhanced by 10.95% and 14.07%, 25.63% and 25.91%, and 39.93% and 35.01% in nano-CuO+DBP and nano-CuO+BBP treatments as compared to the individual exposure groups, verifying that antioxidative defense responses were activated. Furthermore, the co-exposure of nano-CuO and PAEs decreased the population richness and diversity microbiota, and changed the microbial community composition in Daphnia magna. Metabolomic analysis elucidated that nano-CuO + PAEs exposure induced stronger disturbance on metabolic network and molecular function, including amino acid, nucleotides, and lipid metabolism-related metabolic pathways, as comparison to PAEs single exposure treatments. In summary, the integration of physiological, microflora, and untargeted metabolomics analysis offers a fresh perspective into the potential ecological risk associated with nanopollutants and phthalate pollution in aquatic ecosystems.